2012
DOI: 10.20538/1682-0363-2012-6-135-144
|View full text |Cite
|
Sign up to set email alerts
|

Differential mechanical jaundices in ultrasonic diagnosis of parasitic liver problems

Abstract: Проведен сравнительный анализ изменений билиарной системы у 565 пациентов, прооперированных в гепатологическом центре г. Томска, с альвеококкозом, эхинококкозом, хроническим описторхозом, осложненными механической желтухой. Определены три уровня окклюзии и соответствующие виды расширения желчных протоков в зависимости от вовлечения в процесс анатомических структур желчевыводящей системы печени. Выявлены и представлены дифференциальноотличительные ультразвуковые критерии билиарной гипертензии при паразитарных п… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In Belarus, there were five case reports described in Grodno, a city in the border area to Poland and Lithuania [ 64 ], and one post-mortem diagnosis out of Gomel Oblast [ 65 ]. From Russia, the highest figure of 42 AE cases was reported in Tomsk Oblast until 2012 [ 66 ]. Literature focussing on human AE cases in Ukraine could not be found.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Belarus, there were five case reports described in Grodno, a city in the border area to Poland and Lithuania [ 64 ], and one post-mortem diagnosis out of Gomel Oblast [ 65 ]. From Russia, the highest figure of 42 AE cases was reported in Tomsk Oblast until 2012 [ 66 ]. Literature focussing on human AE cases in Ukraine could not be found.…”
Section: Resultsmentioning
confidence: 99%
“…Despite some high estimated figures of more than 1000 new cases annually [ 5 ], there is a distinct lack of data from Russia. Besides numerous single-centre studies with preselected study groups undergoing surgery, epidemiological data could only be found from Moscow [ 94 , 95 ], the south of the Volga and Ural Federal Districts (neighbouring Republic of Bashkortostan and Chelyabinsk Oblast) [ 96 , 97 ], the southwest of Siberia Federal District (Tomsk Oblast, Altai Krai) [ 66 , 98 ] and the Far East Sakha Republic and the peninsula of Kamchatka [ 99 , 100 ]. Nevertheless, the official registry of the Russian federal agency Rospotrebnadzor reported higher figures in 2008 (41 cases) than in 2001 (30 cases) [ 13 , 98 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation